The Commissive Speech Acts Performed by Alma and Mirabel Madrigal in Encanto Movie (2021) - Azka, Mazida Izzatul; Candria, Mytha (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2024)
This study examines the use of commissive speech acts in the Disney animated film Encanto (2021), specifically by the characters Alma and Mirabel Madrigal. This study aims to find out the type of commisive speech act used by Alma and Mirabel in the Encanto (2021) movie. This study also explains the reasons for a certain type of commissive and the language features in the commissive speech acts. Based on the analysis of 16 commissive acts, including guarantee, promising, refusing, volunteering, threatening, and offering, the study finds that guarantee acts are the most frequently used commissive types by the characters, indicating their commitment to future actions. Mirabel performs all of the commissive speech acts to demonstrate her importance and value in the Madrigal family and her ability to stand up for what she believes in. The reasons for these commissive speech acts are mostly to assert the presence of the character or commit to future actions. The language features in commissive speech acts are mostly to make their statement stronger and clearer.Keywords: Characterization; directive speech act; illocutionary act; Sense and Sensibility